2013
DOI: 10.1038/ki.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol restores renovascular function in estrogen-deficient rats through downregulation of cyclooxygenase-2 and the thromboxane-prostanoid receptor

Abstract: Cardiovascular risks increase in postmenopausal women. While vitamin D is supplemented for osteoporosis, it is not known whether it protects renal arterial function during estrogen deficiency. Here we measured changes in renovascular reactivity induced by ovariectomy in rats and examined whether calcitriol, the most active form of vitamin D, was able to correct such changes. The impairment of endothelium-dependent relaxation in renal arteries from ovariectomized rats was effectively reversed by long-term calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
(52 reference statements)
2
23
0
1
Order By: Relevance
“…Therefore, it is suggested that ELD may prevent endothelial dysfunction through the reduction of oxidative stress via normalization of vascular PPARg/NFkB pathway in OVX rats. These beneficial effects of ELD correspond to previous report that calcitriol restored renovascular function in OVX rats (Dong et al 2013). In addition, this is the first report indicated that in vivo endothelial function was evaluated by measurement of FMD under the study design, in which ELD could prevent bone loss in OVX rats.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, it is suggested that ELD may prevent endothelial dysfunction through the reduction of oxidative stress via normalization of vascular PPARg/NFkB pathway in OVX rats. These beneficial effects of ELD correspond to previous report that calcitriol restored renovascular function in OVX rats (Dong et al 2013). In addition, this is the first report indicated that in vivo endothelial function was evaluated by measurement of FMD under the study design, in which ELD could prevent bone loss in OVX rats.…”
Section: Discussionsupporting
confidence: 64%
“…Primary rat aortic endothelial cells were cultured as previously described [25]. Briefly, aortas were isolated, cut open longitudinally, and digested with 0.2% collagenase directed against type 1A collagen (Sigma-Aldrich) for 15 min in a 37°C shaking water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were observed in ex-vivo rat renal arteries treated with U46619, a thromboxane A2 agonist. Here, TEI9647 reduced the phosphorylation of endothelial nitric oxide synthase and levels of NO that were elevated in the presence of 1,25-(OH) 2 D 3 (89). In respect to cancer, TEI9647 reversed the down-regulation of CYP21A2 in the presence of 1,25-(OH) 2 D 3 in a reporter assay using mouse and human adrenocortical carcinoma cells (90).…”
Section: Vdr Antagonists or Allosteric Inhibition Of The Vdr–coregmentioning
confidence: 91%